Wincenty Lutosławski i Juliusz Osterwa: Dzieje kontaktów - Dorota Jarząbek-Wasyl (Pamiętnik Teatralny, 2020)
Based on epistolary material and diaries, the article attempts a reconstruction of the history of Juliusz Osterwa’s (1885–1947) friendship with the famous philosopher Wincenty Lutosławski (1863–1954). Following chronological order, the author presents the circumstances of their meeting in Vilnius in 1925 and the trajectory of their travels and encounters up until Osterwa’s death. With this reconstruction, there emerges a circle of important places, events, and people that influenced both men, e.g. Krakow and the very first productions of Wyspiański’s plays, or Kosów Huculski and Apolinary Tarnawski’s natural therapy facility. The article focuses on the nature of Lutosławski’s and Osterwa’s mutual influence: through their works (writings, acting), direct, personal contact, and the formation of their views, and joint initiatives (particularly important during the occupation, when they both lived in or around Kraków). The text also discusses little-known examples of Lutosławski’s promoting the Reduta theatre abroad. Published as an appendix to the article are Osterwa’s twenty letters and postcards to Lutosławski, dated 1925–1943, from the philosopher collection in the Archive of Science of the Polish Academy of Sciences (PAN) and the Polish Academy of Arts and Sciences (PAU) in Kraków.